1999
DOI: 10.1530/eje.0.1410117
|View full text |Cite
|
Sign up to set email alerts
|

Optimized radioiodine therapy of Graves' disease: analysis of the delivered dose and of other possible factors affecting outcome

Abstract: The best approach to radioiodine dose selection in the treatment of Graves' hyperthyroidism remains highly controversial. The formula to calculate the individual dose of 131 I to be delivered has been used for half a century and takes into account the thyroid mass, the effective half-life and the maximum uptake of 131 I. The objective of the present study was to evaluate the accuracy of this formula by determining the relationship between the administered dose of 131 I calculated to deliver a target dose of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 12 publications
5
50
0
4
Order By: Relevance
“…13 In their study of radioiodine therapy of diffuse goiter, Catargi et al found that mean uptake of a group of patients that remained hyperthyroid after one year follow-up was significantly higher compared to that of the euthyroid group. 20 The significance of our study is that our patients with diffuse toxic goiter received exactly the same dose. The data, therefore, reflect a homogenous treatment modality.…”
Section: Discussionmentioning
confidence: 94%
“…13 In their study of radioiodine therapy of diffuse goiter, Catargi et al found that mean uptake of a group of patients that remained hyperthyroid after one year follow-up was significantly higher compared to that of the euthyroid group. 20 The significance of our study is that our patients with diffuse toxic goiter received exactly the same dose. The data, therefore, reflect a homogenous treatment modality.…”
Section: Discussionmentioning
confidence: 94%
“…Detrimental to any algorithm that includes a 24-h uptake is the great variation in 131 I uptake and turnover over short periods of time (26). In addition, the correlation between the intended and the actual dose delivered to the thyroid is highly variable, with a mean coefficient of variation of 45% (27). It is therefore not surprising that susceptibility of the thyroid to a wide range of 131 I radiation shows huge individual variations (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, several issues need to be clarified, some of which have already been discussed. It is well known that the kinetics of radioiodine changes markedly during 131 I therapy without the use of rhTSH (Catargi et al, 1999;Traino et al, 2000). It was recently shown that the thyroid RAIU during 131 I therapy, in patients with nodular goitre, was lower than the tracer RAIU, but less pronounced when rhTSH pretreatment was employed (Nieuwlaat et al, 2004).…”
Section: Unresolved Issues and Future Perspectivesmentioning
confidence: 99%